Development of Biogas Plant and Mushrooms Grumpy in a Biomass Waste Utilization Facility at Tadukan Raga Village, STM Hilir District, Deli Serdang Regency - Sidabutar, Rivaldi; Trisakti, Bambang; Hanum, Farida; Sarah, Maya; Sinaga, Mersi Suriani; Natasya, Yenny; Ambarita, Renata; Sinamo, Gloria Clarita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service is a form of movement in making a real contribution to society which aims to provide solutions to real problems that occur in society. Most of the Indonesian population still relies on the agriculture, plantation and livestock sectors to drive the economy. By-products in the form of waste are generally used as fertilizer which can actually be used as an alternative energy source. Biogas is a renewable energy produced through the process of anaerobic digestion of organic materials which is currently widely used by the community as an alternative energy to replace LPG for cooking and generator fuel to produce electricity. One of the utilization of non-hazardous biomass waste into energy in the form of biogas has been implemented in Tadukan Raga village in Sinembah Tanjung Muda (STM) Hilir District, Deli Serdang Regency which has been operated since 2018 and is equipped with a barn for mushroom cultivation. However, problems arise where the facility is abandoned where there is a lack of maintenance of biogas generation facilities and mushroom barns, lack of human resources and low understanding of the community, especially BUMDes in the management, development and business maintenance of this facility. Therefore, it is necessary to provide counseling and training to the community in the operation of biogas facilities, revitalize mushroom barns in biomass non-b3 waste utilization facilities and modify LPG stoves into biogas stoves and install stoves in residents' homes around Tungkusan hamlet. Tadukan Raga Village itself is a fostered village that has been used as a place for counseling and service from the University of North Sumatra to the community because there are still several things that need to be improved, so counseling is again carried out in this village.